2019
DOI: 10.1115/1.4044876
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable Locations on the Head to Brain Injury and Implications for Helmet Design

Abstract: In studying traumatic brain injury (TBI), it has been long hypothesized that the head is more vulnerable to injury from impacts in certain directions or locations, as the relationship between impact force and the resulting neurological outcome is complex and can vary significantly between individual cases. Many studies have identified head angular acceleration to be the putative cause of brain trauma, but it is not well understood how impact location can affect the resulting head kinematics and tissue strain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In regard to sport safety interventions, these findings underscore the importance of considering distribution of brain strain in development of the optimal helmet padding. 40 Previous studies have identified the struck player as having higher accelerations on average compared to the striking player. 12,42,43 In this study, players who were struck had greater peak rotational acceleration and brain strain metrics, on average, but players in the striking position had greater mean peak linear acceleration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to sport safety interventions, these findings underscore the importance of considering distribution of brain strain in development of the optimal helmet padding. 40 Previous studies have identified the struck player as having higher accelerations on average compared to the striking player. 12,42,43 In this study, players who were struck had greater peak rotational acceleration and brain strain metrics, on average, but players in the striking position had greater mean peak linear acceleration.…”
Section: Discussionmentioning
confidence: 99%
“…Impacts to the side of the head tend to produce both axial and coronal rotation. 40 It has been found that lateral motion of the falx caused by axial and coronal rotation is associated with corpus callosum trauma in sports-related concussions. 41 Taken together with our findings, impacts to the side of the head pose an increased risk for tissue level injury.…”
Section: Discussionmentioning
confidence: 99%
“…Further examination of impact location can inform optimization of padding placement to minimize rotational angular acceleration in more vulnerable locations. 100 For example, Fanton et al 100 found mandibular impacts to be the most significant. Now that rotational acceleration is becoming a vital consideration of helmet testing, further testing and models to correlate head kinematics (particularly rotational acceleration) with brain strain will be important.…”
Section: Discussionmentioning
confidence: 99%
“…More testing of the different rotational damping helmets is necessary to see which provides the most effective protection against concussions in different settings and at different impact locations. Further examination of impact location can inform optimization of padding placement to minimize rotational angular acceleration in more vulnerable locations [ 99 , 101 ]. For example, Fanton et al [ 101 ] found mandibular impacts to be the most significant.…”
Section: Conclusion Future Directionsmentioning
confidence: 99%